2009
DOI: 10.1080/87565640802564648
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Language Disorders in School-Age Children With Autism

Abstract: Cluster analysis of test scores on expressive phonology and comprehension of words and sentences in 7-9-year-old children with preschool diagnosis of Autistic Disorder yielded 4 clusters. Cluster 1 (N = 11): phonology and comprehension both low; Cluster 2 (N = 4): phonology low, near average comprehension; Cluster 3 (N = 40): average phonology, comprehension low to low average; Cluster 4 (N = 7): average or better phonology and comprehension. The clusters support two major types of language disorders in autism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
114
1
17

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 70 publications
4
114
1
17
Order By: Relevance
“…Unlike Readers with Comprehension Disturbance, Readers with Global Disturbance demonstrated overall low word reading and decoding abilities commensurate with their poor language skills. Similar to children in the Readers with Global Disturbance, the Readers with Severe Global Disturbance resembled Rapin et al (2009) andTager-Flusberg andJoseph's (2003) language impaired subtypes previously described, but with far more severe impairment. The distinction between the two latter profiles may be thought of as categorically distinct areas of a continuum, such as the difference between the terms "below average" and "far below average" that are sometimes used in diagnostic measures.…”
Section: Hfasd Reading Subgroupsmentioning
confidence: 62%
See 3 more Smart Citations
“…Unlike Readers with Comprehension Disturbance, Readers with Global Disturbance demonstrated overall low word reading and decoding abilities commensurate with their poor language skills. Similar to children in the Readers with Global Disturbance, the Readers with Severe Global Disturbance resembled Rapin et al (2009) andTager-Flusberg andJoseph's (2003) language impaired subtypes previously described, but with far more severe impairment. The distinction between the two latter profiles may be thought of as categorically distinct areas of a continuum, such as the difference between the terms "below average" and "far below average" that are sometimes used in diagnostic measures.…”
Section: Hfasd Reading Subgroupsmentioning
confidence: 62%
“…This subgroup has been frequently reported in prior studies of reading with individuals with ASD (e.g., Brown et al 2013;Jones et al 2009;Nation et al 2006;Newman et al 2007;Huemer and Mann 2010;Wei et al 2015;Zuccarello et al 2015) and shares characteristics with a language subgroup reported by Rapin et al (2009) whose members demonstrated adequate phonology and vocabulary alongside linguistic comprehension deficits. Grigorenko et al (2003) noted disagreement in the literature as to whether hyperlexia is synonymous with a reading comprehension disorder, or whether it is a unique condition characterized by an almost obsessive interest in letters and words, precocious and unprompted emergence of word decoding, and an extreme degree of discrepancy between word recognition and other cognitive skills that emerges between 3 and 5 years of age (Healy 1982).…”
Section: Hfasd Reading Subgroupsmentioning
confidence: 85%
See 2 more Smart Citations
“…Also, in a longitudinal study of seven years, Anderson et al (2007) found that at the age of 9 years 29.7% of the children who participated in the study never developed speech. In two other studies (Cleland, Gibbon, Peppé, O'Hare, & Rutherford, 2010;Rapin et al, 2009) 33% of 3 to 9 years old children presented with delayed speech, phonological difficulties and speech disorders that remained even after therapy. Furthermore the percentage of children with ASD who present with feeding disorders reaches 46% to 89% (Ledford & Gast, 2006;Kodak & Piazza, 2008).…”
Section: Discussionmentioning
confidence: 99%